Surgical correction of severe bifid nose - Sinan Ozturk; Fatih Zor; Selcuk Isik (Wolters Kluwer Medknow Publications, 2014)
Craniofacial clefts cause severe facial disfigurement even in minor forms. The surgical reconstruction is imperative to restore function and appearance of facial structures. The presentation of Tessier number: 0 cleft patient may vary from minimal changes on median facial structures such lip, vermilion and nose, and nose to wide clefts dividing all median craniofacial structures. The variability of expression of the unusual orofacial clefts can be challenging for the surgeon, while reconstructing affected facial structures. In this report, we present the surgical management of the case with severe bifid nose. A 27-year-old male presented with congenital midfacial disfigurement with hypertelorism. The patient had a flat nasal dorsum and a deep groove between the two alar domes. The nose was short and bifid. The patient did not accept facial bipartition surgery. We performed de-epithelialization on the skin groove between the two alar domes. We repaired lower one-third part of the nose with native nasal tissues. We reconstructed upper two-third part of the nose with the osteocartilage frame harvested from the calvarium and the nasal septum. Two superiorly based-nasolabial flaps were designed with sufficient length to provide external cover of the osteocartilage frame. In case of the severe bifid nose, osteocartilaginous and soft tissue structures of the nose must be restored separately. Following reconstruction of the osteocartilaginous framework with nasal tissues or grafts, remaining nasal soft tissue, and local flaps can be used to cover the soft tissue.